Issues relating to the low uptake of Networks Of Workstations for commercial applications - Dell, Peter (Edith Cowan University, 2000)
Networks of Workstations are a new approach to parallel computing which promise performance gains and more efficient use of resources, resulting in lower technology costs. Despite these benefits, there are anecdotal reports that the business community has been reluctant to use the technology and that the adoption rate of cluster computing for commercial applications remains extremely low. These anecdotal reports are confirmed. Some concerns preventing the commercial usage of Networks of Workstations are revealed, however these concerns are contrary to the experiences of those organisations that have implemented the technology.